Moderasi Beragama di Pesantren - Irawan, Vaesol Wahyu Eka (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Sekolah Tinggi Islam Blambangan (STIB) Banyuwangi, 2023)
The students in pesantren receive instruction and education to respect Islamic traditions and customs, in addition to Islamic education covering creed, jurisprudence, and morals, such as respecting teachers, so that they are usually educated and disciplined in living their daily lives, and the values of simplicity. Pesantren play an important role in maintaining and preserving Islamic culture and traditions in Indonesia, as well as in shaping the character and morality of the younger generation. The role of santri in moderating society is indeed very strategic, especially in countries with a majority Muslim population. Santri are those who follow Islamic religious education in depth at pesantren or other religious educational institutions. They learn not only about religious teachings, but also values such as tolerance, harmony, and justice.